Active demand response with electric heating systems: Impact of market penetration. (1st September 2016) - Arteconi, Alessia; Patteeuw, Dieter; Bruninx, Kenneth; Delarue, Erik; D'haeseleer, William; Helsen, Lieve
Highlights: Impact of ADR market penetration is analysed. ADR by means of electric heating systems coupled with TES is considered. Different demand side technologies configurations are analysed. Economic benefits for customers and overall system are assessed. An integrated modelling approach for ADR is applied. Abstract: Active demand response (ADR) is a powerful instrument among electric demand side management strategies to influence the customers' load shape. Assessing the real potential of ADR programmes in improving the performance of the electric power system is a complex task, due to the strict interaction between supply and demand for electricity, which requires integrated modelling tools. In this paper an analysis is performed aimed at evaluating the benefits of ADR programmes in terms of electricity consumption and operational costs, both from the final user's and the overall system's perspective. The demand side technologies considered are electric heating systems (i.e. heat pumps and electric resistance heaters) coupled with thermal energy storage (i.e. the thermal mass of the building envelope and the domestic hot water tank). In particular, the effect of the penetration rate of ADR programmes among consumers with electric heating systems is studied. Results clearly show that increasing the number of participating consumers increases the flexibility of the system and, therefore, reduces the overall operational costs. On the other hand, the benefit per individual participant decreases in the presence of more ADR-adherent consumers since a reduced effort from each consumer is needed. Total cost saving ranges at most between about 400 € and 200 € per participant per year for a 5% and 100% ADR penetration rate respectively.